Construindo outros modos de ser e de refletir a docência no ciclo de alfabetização a partir da biologia do amar e da biologia do conhecer de Humberto Maturana - Spanavello, Caroline Silveira (2021)
This research shows the study results made between the year 2017 and 2021 within the Education Post Graduation Program (doctoral) of the Federal University of Santa Maria which has as the main objective to look into the construction of the another way to be an reflect the teaching in the literacy cycle from the Love Biology and the Learn Biology of Humberto Maturana, or, said in another way, look to stablish the relation between the literacy process and the Maturanas’ studies, based on an autobiographical of my own experience as a literacy teacher and researcher during the COVID 19 pandemic context. From this life experience thought and developed by myself during 2020, was possible to stablish some concrete relations about the understanding that the child’s literacy goes through its biology and it is take effect through a mediation of a teacher who enhance emotions based on love and respect for the child’s legitimacy. Therefore, this study was organized from an autobiographical narrative with the main foundation in Abrahão (2003, 2017) and in the written records produced by me, the researcher, by the children and their families during the participation in this teaching, learning, and researching project that happened during the Pandemic scenario. The theoretical foundation used as reference were the studies from de Antunes (2001; 2007; 2013), Maturana (1994; 1997; 1998; 2001; 2004), Barcelos and Maders (2016), Scott and Barcelos (2017), Bellochio and Souza (2017), among others, also the studies developed with the Study and Research Group on Initial, Continuing and Literacy Education (Gepfica in Portuguese), which belongs to the Education Post Graduation Program of the Federal University of Santa Maria of which I have been part since 2016. This study brought to reflection the questions about the ways of being a literacy teacher, looking to understand another ways from the social relation stablished with the child into the perspective of Love Biology and Learn Biology of Humberto Maturana, showing as the main element the role of the literacy teacher, no longer as the responsible for the literacy action (act) but one who, based on the realities, desires and needs of each child, casts sensitive look on them capable of capturing these anxieties and building situation of learning and mediations capable of transforming the action of these children who then build their learning around reading and writing.